Validation of The Business Model of IOT Digital Industry-Class Services - Adelia Octaviana M; Ghina, Astri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study investigates KIDI IoT, an educational service by PT Telkom Indonesia designed to bridge the skills gap between Vocational High School (SMK) graduates and the demands of the Industry 4.0 workforce. The primary objective was to assess the extent to which the KIDI IoT service fulfilled the requirements of educators and learners to substantiate its value proposition. A qualitative, exploratory methodology was employed utilizing in-depth interviews and the Value Proposition Canvas (VPC) framework for analysis. The outcomes demonstrate how effectively the program's project-based, experiential approach increases user motivation and offers a practical, industry-relevant learning environment. The service successfully generates the desired customer benefits. A major customer pain point that the current model ignores is that participants often expressed that the two-day offline training period was insufficient to help them master the material or build their confidence for working independently. This led to a significant misalignment. The KIDI IoT value proposition is fundamentally strong and well-regarded; however, the study concludes that its implementation necessitates improvement, particularly through the provision of more specialized teacher training and an extended training duration, to ensure sustained impact and skill acquisition.